Problems and Legal Protection of Art Works in Non-Fungible Token (NTF) Practices - Wijaya, Niko; Urbaniasi, Urbaniasi (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This article analyzes the Non-Fungible Token, abbreviated NFT, which is a digital certificate that can be used to verify who owns certain assets in the world of crypto art, where this certificate represents ownership of authentic works of art. Non-Fungible Token (NFT) as a digital asset as well as several legal issues that arise related to NFTs, especially in the field of intellectual property law including copyright protection and legal construction of copyright ownership of NFTs. This study uses a normative legal research method with a statutory approach. This study aims to find out how the legal problems in the practice of intellectual property development commercialization of non-fungible tokens (NFT) and how to protect works of art in the form of Indonesian non-fungible tokens (NFT). The results of this study indicate that although in Indonesia there are no specific regulations that explicitly regulate Non-Fungible Tokens (NFT), the rights of creators of works are generally protected by Law Number 28 of 2014 concerning Copyright, but from an intellectual point of view property development, NFT presents the potential for the development and commercialization of works through digital media that has a wide reach and provides more optimal monetization opportunities.